A Positron Implantation Profile Estimation Approach for the PALS Study of Battery Materials - Xin Li; Bernardo Barbiellini; Vito Di Noto; Gioele Pagot; Meiying Zheng; Rafael Ferragut (Condensed Matter, 2023)
Positron annihilation spectroscopy is a powerful probe to investigate the interfaces in materials relevant for energy storage such as Li-ion batteries. The key to the interpretation of the results is the positron implantation profile, which is a spatial function related to the characteristics of the materials forming the battery. We provide models for the positron implantation profile in a cathode of a Li-ion battery coin cell. These models are the basis for a reliable visualization of multilayer geometries and their interfaces in thin cathodes of lithium-ion batteries.